The Impact of Globalization on Borrowing Word in Local Languages in Indonesia - Tariqatul Laily (PT FORMOSA CENDEKIA GLOBAL, 2024)
Globalization has become an unavoidable phenomenon in this modern era, and its impact on various aspects of life, including language, is very significant. In Indonesia, globalization affects the borrowing of words from foreign languages into local languages. This process involves not only the use of new words but also the transformation of meaning and usage in the context of local culture. This study aims to explore how globalization borrows words into local languages in Indonesia, with a focus on the factors that drive such borrowing and its impact on the linguistic identity of the community. Through qualitative analysis and case studies, it is found that word borrowing is often triggered by the need for broader communication, the influence of mass media, and increased social interaction with the outside world. However, despite the benefits of enriching the nail, there are also risks to the preservation of local languages and cultural identity.